The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bjophthalmol-2020-317664
|View full text |Cite
|
Sign up to set email alerts
|

Myopia control effect of defocus incorporated multiple segments (DIMS) spectacle lens in Chinese children: results of a 3-year follow-up study

Abstract: AimsTo determine myopia progression in children who continued to wear the defocus incorporated multiple segments (DIMS) lenses or switched from single vision (SV) to DIMS lenses for a 1-year period following a 2-year myopia control trial.Methods128 children participated in this study. The children who had worn DIMS lenses continued to wear DIMS lenses (DIMS group), and children who had worn SV lenses switched to wear DIMS lenses (Control-to-DIMS group). Cycloplegic spherical equivalent refraction (SER) and axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 26 publications
(36 reference statements)
4
116
0
6
Order By: Relevance
“…A further report has shown that this myopia control effect is sustained in the third year. 13,27 While study design differences make direct comparison difficult, the RLRL efficacy results reported here appear at least competitive with these other treatment modalities.…”
Section: Efficacy In Comparison With Other Treatmentsmentioning
confidence: 84%
See 1 more Smart Citation
“…A further report has shown that this myopia control effect is sustained in the third year. 13,27 While study design differences make direct comparison difficult, the RLRL efficacy results reported here appear at least competitive with these other treatment modalities.…”
Section: Efficacy In Comparison With Other Treatmentsmentioning
confidence: 84%
“…The inclusion and exclusion criteria adopted were the same as for the majority of myopia control trials conducted for low dose atropine eyedrops 12 and defocus incorporated multiple segments (DIMS) spectacle lens 13 , in order to ensure outcomes were comparable across studies. Eligible participants were children aged 8 to 13 years with myopia of cycloplegic spherical equivalent refraction (SER) of -1.00 to -5.00 diopters (D), astigmatism < 2.50 D, anisometropia < 1.50 D, best-corrected visual acuity (BCVA) > 0.0 logMAR (Snellen 1.0 or 20/20) in either eye, and were willing to J o u r n a l P r e -p r o o f participate in the study and accept random allocation in grouping.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…In addition to genetic susceptibility, several environmental factors, such as prolonged near work, increased digital screen time, and insufficient time spent outdoors, are recognized as important risk factors for myopic progression [1][2][3][4]. To control the epidemic of myopia, low-concentration atropine eye drops and specially designed contact lenses and spectacle lenses, such as defocus incorporated multiple segments (DIMS) lenses and aspherical lenslets, are recommended to reduce myopic progression and have now reached high levels of evidence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Zusätzlich sind in Abb. 3 die aus aktuellen Studiendaten ermittelten mittleren Wachstumsraten der Studien zu den DIMS-Gläsern [ 18 , 20 ], aus der LAMP-Studie (Yam et al. 2020) zur Wirkung von Atropin-Augentropfen auf die Myopieprogression [ 35 ], aus der ROMIO-Studie (Cho et al.…”
Section: Bisherige Studienergebnisseunclassified
“…Gemäß Abb. 3 , nach aktueller Studienlage, erfüllt allein die DIMS-Brille im Beobachtungszeitraum [ 18 , 20 ] das hier vorgestellte praktische Therapiekriterium vollständig, während die Therapie mit 0,05 % Atropin [ 35 ] und danach die Ortho-K-Therapie [ 10 ] und die Therapie mit „High Add“-multifokalen Kontaktlinsen [ 29 ] eine noch tolerierbare Therapieperformance erreichen können. Wie aber kürzlich von Joachimsen et al berichtet [ 14 ], müsse eine Atropin-Konzentration von 0,05 % bei kaukasischen Kindern aufgrund der Nebenwirkungen in der praktischen klinischen Anwendung als kritisch eingestuft werden.…”
Section: Alternative Zu Bekannten Therapieoptionen?unclassified